2020
DOI: 10.1016/j.jobcr.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Is there evidence for Novamin application in remineralization?: A Systematic review

Abstract: Background: Calcium sodium phosphor-silicate material, a type of bio-glass was originally developed as an implant material to regenerate bone and recently adapted for use in oral care products (NovaMin Technology Inc.). Novamin is used for many dental problems like hypersensitivity, gingivitis, bleeding, non-carious lesions, carious lesions, whitening and is currently emerging as one of the treatment modality for the remineralization of the tooth. Since the prescription of these novel materials to the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…9,16,17,18,19 NovaMin is an inorganic and synthetic compound, which releases sodium, calcium, phosphate, and silica when it exposed to an aqueous media, increases pH and forms Hydroxycarbonateapatite crystals, and thus initiates the remineralization process. 20,21,22 The pairwise comparisons showed of this study illustrate that there are no statistically significant differences between NovaMin and fluoride in SMH values. Although NovaMin did not offer further remineralization effect than did fluoride, this study shows it equally beneficial.…”
Section: Discussionmentioning
confidence: 54%
“…9,16,17,18,19 NovaMin is an inorganic and synthetic compound, which releases sodium, calcium, phosphate, and silica when it exposed to an aqueous media, increases pH and forms Hydroxycarbonateapatite crystals, and thus initiates the remineralization process. 20,21,22 The pairwise comparisons showed of this study illustrate that there are no statistically significant differences between NovaMin and fluoride in SMH values. Although NovaMin did not offer further remineralization effect than did fluoride, this study shows it equally beneficial.…”
Section: Discussionmentioning
confidence: 54%
“…Krithi [ 34 ], on one hand, also demonstrated that sodium fluoride (NaF) showed improvement in bond strength results. On the other hand, the authors stressed the need for more studies regarding NovaMin [ 34 ], a type of bioglass composed of calcium sodium phosphor-silicate and usually indicated for dentin hypersensitivity [ 60 ]. Since remineralizing agents have a vast intervention field in operative dentistry and very few studies investigated these agents, further studies should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The authors recommended better-designed clinical trials to make definitive recommendations about this technology. 27 The toothpaste containing proprietary REFIX technology, according to the manufacturer, represents a novel, multifunctional, phosphate-based dental gel technology in an acidified stabilized phosphate/fluoride complex which is established especially in saliva. 13 The combination of toothpaste, saliva, and dental tooth structures favors the generation of new minerals containing calcium/phosphate/fluorine, promoting the enamel surface, and remineralizing within the subsurface carious lesion.…”
Section: Discussionmentioning
confidence: 99%